Secure key-sharing algorithm based on smart grid - Wei GU; Jian SHEN; Yongjun REN (网络与信息安全学报)
Most of establishment-key protocols suffer from both session-specific temporary information attack and private key leakage issue.Therefore, a novel public key sharing-based symmetric encryption algorithm (PKS-SE) was proposed, in order to maintain the security of communication between smart meter and service providers.Based on bilinear mapping and super-singular curve, PKS-SE algorithm constructed the communication key between intelligent electricity meter and service provider, in order to avoid the key escrow problem.At the same time, PKS-SE algorithm reduced the number of required messages during the mutual authentication to only two messages, thus controlling the communication cost and operation cost of PKS-SE algorithm.Simulation results show that the proposed PKS-SE algorithm can effectively realize public key-sharing